ACCOUNTING BALANCE AND REPORTING (Intent Research Scientific Journal, 2023)
In today's dynamic business environment, accurate financial reporting plays an important role in providing stakeholders with critical information for decision making. Among the main financial statements, the balance sheet stands out as the main document that provides a snapshot of the company's financial health at a given point in time. This article aims to explore the importance of balance sheet reporting, concluding with its definition, key words, introduction, methods, results, discussion and suggestions for effective implementation.